Concomitant gain of 1q21 and MYC translocation define a poor prognostic subgroup of hyperdiploid multiple myeloma - Weinhold, Niels; Kirn, Désirée; Seckinger, Anja; Hielscher, Thomas; Granzow, Martin; Bertsch, Uta; Egerer, Gerlinde; Salwender, Hans; Blau, Igor W.; Weisel, Katja; Hillengaß, Jens; Raab, Marc-Steffen; et al. (Haematologica, 2016)
The impact of MYC locus aberrations on the outcome of multiple myeloma (MM) patients is still a matter of debate. The aim of this study was to further investigate their influence on the survival of MM patients treated with high-dose chemotherapy. Our data suggest that the favorable prognosis factor
Gesehen am 21.02.2020